Inter Faces: creation processes for artistic performance enhanced by augmented reality - Oliveira, Régis Costa de; Mendes, Mónica Sofia Santos; Paiva, Anselmo Cardoso de (Revista Brasileira de Estudos da Presença, 2020)
Inter Faces: creation processes for artistic performance enhanced by augmented reality – In view of the poetic use of augmented reality, this article presents links between performance and augmented reality technology with self-referenced digital content, supported by the activist artistic proposal Inter Faces. For a reflection on creative processes, the artistic works body and Parade to Hope are compared. With this analysis we intend to present the challenges and solutions found during the creation process of Inter Faces, seeking to contribute to the debate on the expansion, popularization and poetization of augmented reality in performance.